ESTABLISHMENT OF THE SUBSIDIARY MANAGEMENT CORPORATION IN THE INTEGRATED DEVELOPMENT - Tan Wee Vern; Tan Liat Choon; Looi Kam Seng; Toh Ming Liang; Shanmugapathy A/L Kathitasapathy; Muhamad Uznir Bin Ujang; Nor Suhaibah Binti Azri; Thoo Ai Chin (Journal of Islamic, Social, Economics and Development, 2022)
The establishment of the subsidiary management corporation is low in Malaysia, even though it was introduced in the legislation. Hence, this research aims to examine the importance of establishment of the subsidiary management corporation. The integrated development consists of different usages of development under a strata scheme, therefore, it is suitable to establish subsidiary management corporation to manage the limited common property which is designated to the owner who has interest or exclusive benefit on it. The determination of the importance of the establishment of the subsidiary management corporation is according to the opinion of the owners or residents in the integrated development. As the consequences, the selection of respondents in this research is the owners or residents in the integrated development in Malaysia by applying the random sampling method. A total of 100 respondents are selected randomly in this research, while the analysis of the opinion of the respondents is applying the descriptive statistical analysis. Results show that the subsidiary management corporation is significant to be established in an integrated development due to the complexity management in an integrated development as well as some common properties do not enjoyable by all the proprietors. Therefore, the establishment of the subsidiary management corporation is vital in an integrated development. However, the importance of the establishment of the subsidiary management corporation do not reflect in the current trend of the integrated development in Malaysia, hence, the enhancements are significant to promote the establishment of the subsidiary management corporation in Malaysia.